Class I in a nutshell: Malaysian Association of orthodontists postgraduate study day - Abu Bakar, Noraini (2022)
Dental malocclusions are classified based on the molar position and incisor relationships. In a nutshell, Class I malocclusion would mean that the molars and the incisors are in correct position but there are some other discrepancies presented such as crowding, spacing, tooth impaction, crossbite etc. This brief lecture will give an overview of Class I malocclusion with a few examples of cases and its clinical management.